Anti-obesity effects of chikusetsusaponins isolated from Panax japonicus rhizomes - Okuda Hiromichi; Yoshikawa Masayuki; Zheng Yi-Nan; Han Li-Kun; Kimura Yoshiyuki (BMC, 2005)
Abstract Background The rhizomes of Panax japonicus are used as a folk medicine for treatment of life-style related diseases such as arteriosclerosis, hyperlipidemia, hypertension and non-insulin-dependent diabetes mellitus as a substitute for ginseng roots in China and Japan. Obesity is closely associated with life-style-related diseases. This study was performed to clarify whether chikusetsusaponins prevent obesity induced in mice by a high-fat diet for 9 weeks. Methods We performed two in vivo experiments. In one, female ICR mice were fed a high-fat diet with or without 1 or 3% chikusetsusaponins isolated from P. japonicus rhizomes for 9 weeks. In the other, lipid emulsion with or without chikusetsusaponins was administered orally to male Wistar rats, and then the plasma triacylglycerol level was measured 0.5 to 5 h after the orally administered lipid emulsion. For in vitro experiments, the inhibitory effects of total chikusetsusaponins and various purified chikusetsusaponins on pancreatic lipase activity were determined by measuring the rate of release of oleic acid from triolein in an assay system using triolein emulsified with lecithin. Results Total chikusetsusaponins prevented the increases in body weight and parametrial adipose tissue weight induced by a high-fat diet. Furthermore, consumption of a high-fat diet containing 1 or 3% total chikusetsusaponins significantly increased the fecal content and triacylglycerol level at day 3 compared with the high-fat diet groups. Total chikusetsusaponins inhibited the elevation of the plasma triacylglycerol level 2 h after the oral administration of the lipid emulsion. Total chikusetsusaponins, chikusetsusaponin III, 28-deglucosyl-chikusetsusaponin IV and 28-deglucosyl-chikusetsusaponin V inhibited the pancreatic lipase activity. Conclusion The anti-obesity effects of chikusetsusaponins isolated from P. japonicus rhizomes in mice fed a high-fat diet may be partly mediated through delaying the intestinal absorption of dietary fat by inhibiting pancreatic lipase activity. The present study clearly indicated that the saponin fractions of P. japonicus rhizomes had a significant anti-obesity action and supports the traditional usage as a substitute drug for ginseng roots.